Enhancing Perovskite Electrocatalysis of Solid Oxide Cells Through Controlled Exsolution of Nanoparticles - Hua, Bin; Li, Meng; Sun, Yi‐Fei; Li, Jian‐Hui; Luo, Jing‐Li (ChemSusChem, 2017)
Perovskite oxides have received a great deal of attention as promising electrodes in both solid oxide fuel cells (SOFCs) and solid oxide electrolyzer cells (SOECs) because of their reasonable reactivity, impurity tolerance, and tunable properties. In particular, exploration is still required for improving perovskite electrodes, which normally suffer from slow kinetics in electrocatalysis. Experimental studies have led to the development of new classes of perovskites with advanced characteristics and electrode kinetics at technical levels. In parallel with those developments, achievements in theoretical and computational studies have led to substantial understanding, at the atomic level, of their physicochemical properties and electrocatalytic behaviors. Their chemical and structural flexibilities enable perovskites to accommodate most metallic elements without destroying their complex matrix structures, thereby delivering a pathway to engineer their catalytic properties. In this Minireview, recent advances in perovskite electrodes are introduced, and perovskites with exsolved nanoparticles are discussed as enhanced electrocatalytic materials. Excellent exsolution: In this Minireview, perovskites with exsolved nanoparticles are examined as enhanced electrocatalytic materials for solid oxide cells. Nanoparticle exsolution is among the most promising techniques for future catalysis and energy technologies in sustainable systems. In light of its great advantages, this strategy has received much attention for developing suitable electrocatalysts for a wide range of applications.